The Impacts of the Dollar-Renminbi Exchange Rate Misalignment on the China-United States Commodity Trade: An Asymmetric Analysis - Sabrine Ferjani; Sami Saafi; Ridha Nouira; Christophe Rault (Institute of Labor Economics (IZA), 2022)
Contrary to most existing studies of the literature that assumed that the effects of real exchange rate (RE) misalignment on trade flows are symmetric, this paper considers a more general and realistic framework allowing for possible asymmetric effects. We use monthly time-series data over the January 2002-October 2020 period from 66 two-digit industries that trade between China and the U.S. in order to avoid the well-known aggregation bias. Estimates of symmetric error-correction models (ECM) revealed that real dollar-renminbi rate misalignment has short-run effects on 35 U.S. exporting and 53 U.S. importing industries. These short-run effects translated into the long run in 18 and 17 industries, respectively. The numbers increased considerably when estimating asymmetric ECM. Indeed, short-run asymmetric effects were then found in 47 U.S. exporting and 62 U.S. importing industries, which translated into long-run asymmetric effects in 20 U.S. exporting and 21 U.S. importing industries. Our analysis highlights the importance of separating currency overvaluation from currency undervaluation in assessing the effects of the RE misalignment on trade flows between the U.S. and China and confirms that the impacts are industry specific. Our findings (robust to possible structural breaks) are useful for trading industries, and policymakers, and advocate accounting for asymmetries when examining the RE misalignment-trade flows nexus.
Keywords: F14; F31; C10; 330; asymmetry; nonlinear ARDL; exchange rate misalignment; commodity trade; China; the United States